A high-strength and high-toughness dual-phase titanium alloy with multi-level α-phase structure and a preparation method thereof

Through the design of a high-strength, high-strength, dual-phase titanium alloy with multi-layered alpha-phase structure through component modification and thermal deformation processes, the shortcomings of existing titanium alloys in terms of strength and toughness and impact toughness are solved, and excellent comprehensive mechanical properties are achieved.

CN117026010BActive Publication Date: 2025-04-04NORTHWESTERN POLYTECHNICAL UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311096668.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-08-29
Publication Date
2025-04-04
Estimated Expiration
2043-08-29

AI Technical Summary

Technical Problem

Existing titanium alloys have shortcomings in comprehensive mechanical properties such as strength and toughness, especially in impact toughness.

Method used

Through component modification and thermal deformation technology, a high-strength and high-tough biphasic titanium alloy with multi-layered alpha-phase structure was designed, with specific components: Al: 4.8%-5.2%, V: 7.3-7.8%, Si: 0.3-0.5%, and Mo: 0.8-1.1%. Multi-pass hot rolling treatment and multi-stage heat treatment system were used to regulate the microstructure of the titanium alloy.

Benefits of technology

The high tensile strength, yield strength and elongation after break of titanium alloy are achieved, and its impact toughness is significantly improved, achieving the performance of tensile strength greater than 1250MPa, yield strength greater than 1150MPa, elongation after break of more than 8%, and impact toughness greater than 35J/cm2.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117026010B_ABST
    Figure CN117026010B_ABST
Patent Text Reader

Abstract

The present application discloses a high-strength and high-toughness dual-phase titanium alloy with a multi-level α-phase structure and a preparation method thereof, wherein the mass percentage of the titanium alloy elements is as follows: Al: 4.8%-5.2%, V: 7.3-7.8%, Si: 0.3-0.5%, Mo: 0.8-1.1%, the remainder is Ti and impurity elements, and the mass percentages of the Al, V, Mo, and Si elements must satisfy the following relationship:; Its preparation method includes: batching according to the above-mentioned component ratio, and obtaining an initial titanium alloy ingot by smelting; the initial titanium alloy ingot is subjected to multiple hot rolling processes to obtain a titanium alloy rolled plate; the titanium alloy rolled plate is subjected to vacuum pressurization leveling treatment, stress relief annealing treatment, solution treatment, and aging treatment to obtain the final high-strength and high-toughness dual-phase titanium alloy with a multi-level α-phase structure. The present invention first adds an appropriate amount of Mo element, and then obtains a multi-level α phase through a multi-pass small deformation variable temperature rolling process and a multi-stage heat treatment system to improve the deformation coordination ability and impact toughness of the alloy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of titanium alloy structure control, and specifically relates to a high-strength and high-toughness dual-phase titanium alloy with a multi-level α-phase structure and a preparation method thereof. Background Art

[0002] Structural materials in the field of military equipment need to have excellent strength, toughness, and good plasticity. In order to meet the requirements of structural materials for mechanical properties, it is necessary to take into account the matching between strength, plasticity, and toughness. The tensile strength of the high-strength and toughness α+β titanium alloy TC21 currently used in my country can be greater than 1200MPa, and the elongation after fracture can reach more than 12%, but its impact toughness generally does not exceed 25 J / cm 2 Generally speaking, in order to make titanium alloy parts have excellent strength and toughness, it is necessary to obtain the ideal microstructure through appropriate hot working process. Summary of the invention

[0003] Aiming at the deficiencies of some commonly used titanium alloys in comprehensive mechanical properties such as strength and toughness, the present invention designs a high-strength and high-toughness dual-phase titanium alloy with a multi-level α-phase structure and a preparation method thereof based on the principles of composition modification and thermal deformation process strengthening.

[0004] Specifically, the first aspect of the present invention provides a high-strength and high-toughness dual-phase titanium alloy with a multi-level α-phase structure, wherein the mass percentages of the titanium alloy elements are as follows: Al: 4.8%-5.2%, V: 7.3-7.8%, Si: 0.3-0.5%, Mo: 0.8-1.1%, and the remainder is Ti and impurity elements, and the mass percentages of Al, V, Mo, and Si elements must satisfy the following relationship:

[0005] ;

[0006] Among them, W Al , W Si , W V , W Mo They represent the mass percentages of Al, Si, V and Mo elements respectively.

[0007] Furthermore, the titanium alloy has a tensile strength greater than 1250 MPa, a yield strength greater than 1150 MPa, a fracture elongation greater than 8%, and an impact toughness greater than 35 J / cm 2 .

[0008] Furthermore, the titanium alloy structure includes equiaxed α p phase, rod-shaped α sheets and β transformation matrix, and the β transformation matrix contains fine secondary α phase.

[0009] Furthermore, the isometric axis αp The volume fraction of the phase is 15% to 25%, and the volume fraction of the rod-like α sheet is 34% to 45%.

[0010] A second aspect of the present invention provides a method for preparing a high-strength and high-toughness dual-phase titanium alloy having a multi-level α-phase structure, comprising:

[0011] The ingredients are prepared according to the composition ratio of the high-strength and high-toughness dual-phase titanium alloy, and an initial titanium alloy ingot is obtained by smelting;

[0012] The initial titanium alloy ingot is subjected to multiple hot rolling processes to obtain a titanium alloy rolled plate;

[0013] The titanium alloy rolled plate is subjected to vacuum pressurization leveling treatment, stress relief annealing treatment, solution treatment and aging treatment to obtain a final high-strength and high-toughness dual-phase titanium alloy with a multi-level α phase structure.

[0014] Furthermore, the multi-pass hot rolling process includes:

[0015] The initial titanium alloy ingot is placed in a heat treatment furnace at 800°C~830°C, and immediately rolled to 930°C~970°C after being heated to 930°C~970°C, and then returned to the furnace for insulation for 5min~8min between passes. The initial titanium alloy ingot is then cooled to 880°C~900°C with the furnace, and after insulation for 5min~10min, it is rolled for three more passes and finally quenched, and returned to the furnace for insulation for 5min~8min between passes. The total rolling deformation is 70%~80%.

[0016] Furthermore, the stress relief annealing treatment is performed at 560° C. to 600° C. for 3 h to 5 h.

[0017] Furthermore, the solution treatment is to subject the rolled plate after stress relief annealing to solution treatment at 850°C-870°C for 1h and then air-cool it.

[0018] Furthermore, the aging treatment is to keep the rolled plate after solution treatment and air cooling at 800°C~830°C for 0.5h, then cool it to 760°C~790°C with the furnace and air cool it, and then perform aging treatment at 500°C~550°C for 5h~8h and then air cool it.

[0019] Compared with the prior art, the present invention has the following beneficial technical effects:

[0020] The present invention is first based on the principle of composition modification. By adding an appropriate amount of Mo element, the structure is refined, the strength of the alloy is improved, and the Mo equivalent is increased; then, through a multi-pass small deformation variable temperature rolling process and a multi-stage heat treatment system, the interactive mechanism of recrystallization and phase transformation of titanium alloy under thermal-mechanical coupling conditions is utilized to obtain a multi-level α phase to improve the deformation coordination ability and impact toughness of the alloy.

[0021] In summary, the titanium alloy provided in this application has relatively excellent strength and toughness and relatively outstanding comprehensive mechanical properties, and will have relatively broad application prospects and development potential in various fields of industry. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is the SEM image of the titanium alloy structure obtained in Example 1 of the present application.

[0023] Figure 2 This is a high-magnification SEM image of the titanium alloy structure obtained in Example 1 of the present application.

[0024] Figure 3 This is a tensile fracture morphology diagram of the titanium alloy in Example 1 of the present application; wherein, Figure 3 (a) is a low-magnification SEM image of the tensile fracture; Figure 3 (b) is a high-magnification SEM image of the tensile fracture.

[0025] Figure 4 This is the SEM image of the titanium alloy structure obtained in Example 2 of the present application. DETAILED DESCRIPTION

[0026] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0027] In titanium alloys, α p and α s The volume fraction, size, distribution and morphology of the titanium alloy greatly affect mechanical properties such as impact toughness. The hot working process spheroidizes the α phase and also improves the comprehensive mechanical properties; therefore, obtaining a multi-level α phase structure is of vital importance to improving the comprehensive mechanical properties of titanium alloys. In summary, if a new high-strength and high-toughness α+β dual-phase titanium alloy with a multi-level α phase structure can be developed as a material for new weapon equipment structural parts by designing new components and combining hot working technology to regulate the organization, it is expected to promote the popularization of titanium alloys in military equipment in multiple fields.

[0028] Based on the above considerations, this application aims at the deficiencies of some commonly used titanium alloys in comprehensive mechanical properties such as strength and toughness in applications. Based on the principles of composition modification and hot deformation process strengthening, a high-strength and high-toughness dual-phase titanium alloy with a multi-level α phase structure is designed. The mass percentages of the elements in the titanium alloy are as follows: Al: 4.8%-5.2%, V: 7.3-7.8%, Si: 0.3-0.5%, Mo: 0.8-1.1%, and the remainder is Ti and impurity elements, and the mass percentages of Al, V, Mo, and Si elements must satisfy the following relationship:

[0029] ;

[0030] Among them, W Al , W Si , W V , W Mo They represent the mass percentages of Al, Si, V and Mo elements respectively.

[0031] The high-strength and high-toughness dual-phase titanium alloy with a multi-level α-phase structure may, for example, be composed of the following components in percentage by mass: Al: 5.16%, V: 7.47%, Si: 0.47%, Mo: 0.93%, and the remainder being Ti and impurity elements.

[0032] The high-strength and high-toughness dual-phase titanium alloy with a multi-level α-phase structure may, for example, be composed of the following components in percentage by mass: Al: 5.07%, V: 7.62%, Si: 0.42%, Mo: 0.95%, and the remainder being Ti and impurity elements.

[0033] The method for preparing the high-strength and high-toughness dual-phase titanium alloy having a multi-level α-phase structure comprises the following steps:

[0034] S101: preparing the ingredients according to the composition ratio of the high-strength and high-toughness dual-phase titanium alloy, and obtaining an initial titanium alloy ingot by smelting.

[0035] Specifically, titanium sponge, high-purity aluminum blocks, high-purity vanadium sheets, high-purity silicon particles and zirconium sponge are weighed according to the mass percentage of the elements to prepare the ingredients, and after six smelting passes in a vacuum non-consumable arc furnace (the last three passes use magnetic stirring), an initial titanium alloy cast ingot is obtained.

[0036] S102: subjecting the initial titanium alloy ingot to a multi-pass hot rolling process to obtain a titanium alloy rolled plate.

[0037] In some embodiments, the multi-pass hot rolling process specifically includes: placing the initial titanium alloy ingot into a heat treatment furnace at 800°C to 830°C (for example, 800°C, 810°C, 820°C, 830°C, etc.), heating the furnace to 930°C to 970°C (for example, 930°C, 940°C, 950°C, 960°C, 970°C, etc.), and then immediately rolling the initial titanium alloy ingot for two passes, returning to the furnace for insulation for 5min to 8min (for example, 5min, 6min, 7min, 8min, etc.) between passes, and The initial titanium alloy ingot is then furnace cooled to 880°C~900°C (for example, 880°C, 890°C, 900°C, etc.), kept warm for 5min~10min (for example, 5min, 7min, 8min, 10min, etc.), rolled three times and finally quenched, returned to the furnace for keeping warm for 5min~8min between passes (for example, 5min, 6min, 7min, 8min, etc.), and the total rolling deformation is 70%~80% (for example, 70%, 73%, 76%, 80%, etc.).

[0038] The heat treatment furnace is preferably a box-type furnace; the two hot rolling passes are preferably carried out on a two-roll rolling mill; the cumulative deformation of the two hot rolling passes is preferably 30%; and the cumulative deformation of the three hot rolling passes is preferably 50%.

[0039] S103: performing vacuum pressurization leveling treatment and stress relief annealing treatment on the titanium alloy rolled plate.

[0040] Specifically, the stress relief annealing treatment is performed at 560° C. to 600° C. (eg, 560° C., 570° C., 580° C., 600° C., etc.) for 3 h to 5 h (eg, 3 h, 4 h, 5 h, etc.).

[0041] In some embodiments, the vacuum pressure leveling and stress relief annealing treatment specifically includes: placing the rolled plate in a vacuum diffusion welding furnace, evacuating the vacuum until the vacuum degree reaches 1×10 -3 After Pa, the temperature is raised to 580℃, pressurized for 2T and kept warm for 4h, the rolled plate is leveled and stress-relief annealed, and then taken out after furnace cooling.

[0042] S104: subjecting the titanium alloy rolled plate to a solution treatment and an aging treatment to obtain a final high-strength and high-toughness dual-phase titanium alloy having a multi-layered α-phase structure.

[0043] The solution treatment is to perform a 1h solution treatment on the rolled plate after stress relief annealing at 850℃~870℃ (for example, 850℃, 860℃, 870℃, etc.) and then air-cool. The aging treatment is to keep the rolled plate after solution treatment at 800℃~830℃ (for example, 800℃, 810℃, 820℃, 830℃, etc.) for 0.5h and then cool it to 760℃~790℃ (for example, 760℃, 770℃, 780℃, 790℃, etc.) with the furnace and then air-cool it, and then perform an aging treatment at 500℃~550℃ (for example, 500℃, 510℃, 520℃, 530℃, 540℃, 550℃, etc.) for 5h~8h (for example, 5h, 6h, 7h, 8h, etc.) and then air-cool it.

[0044] The above-mentioned solution treatment and aging treatment are preferably carried out in a box furnace.

[0045] The present application is first based on the strength and toughness of the α+β two-phase titanium alloy strengthened by composition modification. As an important isomorphous β stabilizing element, the Mo element can significantly improve the room temperature and high temperature strength of the titanium alloy and enhance thermal stability. Generally speaking, the higher the content of the Mo element, the better the hardenability of the titanium alloy. High-strength titanium alloys, high-temperature titanium alloys, etc. all contain a large amount of Mo elements. However, if the content of the Mo element is too high, Mo segregation or Mo inclusions are easily formed in the titanium alloy. The appropriate addition of the Mo element can better achieve the strong and tough combination of the titanium alloy and improve its impact toughness. The Mo element can play a role in refining grains and refining the organization in the titanium alloy, and can promote the generation of cross-distributed α sheets, so that the ability to resist crack propagation during deformation is improved, and its impact toughness is improved. Therefore, the present application adds about 0.8% to 1.1% of the Mo element, while achieving the refinement of the organization and realizing fine grain strengthening, appropriately improves the Mo equivalent of the titanium alloy, improves its hardenability, and provides a strengthening basis for subsequent solution aging treatment. In addition, the present application also summarizes the mass percentage relationship that the Al element, Si element, Mo element and V element need to satisfy through experimental verification and empirical formula:

[0046]

[0047] By calibrating this formula, the content of alloying elements added to the titanium alloy can be controlled within a certain range, which can better adjust the deformation coordination relationship between the α phase and the β phase in the dual-phase titanium alloy, and ultimately achieve a balance between various properties.

[0048] Secondly, a multi-layered α phase is obtained through a cross-phase region multi-pass small deformation variable temperature rolling process combined with a subsequent multi-stage heat treatment system to improve the deformation coordination ability of the alloy. The initial titanium alloy ingot obtained by smelting has defects such as uneven structure, component segregation, and coarse grains. By first heating the ingot to the β single-phase region for two hot rolling passes, the coarse β grains can be flattened and broken, and elongated along the metal deformation flow direction, eliminating the influence of the uneven cast structure on its subsequent mechanical properties, and also reducing its deformation resistance and cracking tendency during rolling. After the ingot is rolled twice in the β single-phase region, it is quickly returned to the furnace to cool to 880℃~900℃ with the furnace, and then rolled three times and quenched. The grain boundary α phase precipitated during the cooling process of the ingot in the furnace and the lamellar α phase precipitated in the grains continue to be deformed during the subsequent two-phase region rolling process. The lamellar α phase is twisted, broken and arranged along the deformation direction. Dynamic recrystallization occurs in this process, and spherical α grains are formed on the grain boundaries and in the grains. The quenched rolled plate is then subjected to vacuum pressure leveling treatment to facilitate subsequent machining of standard mechanical properties specimens. Because the alloy accumulates a large amount of strain energy during the rolling process, it is necessary to perform stress relief annealing at 560℃~600℃ for 3h~5h to release some of the strain energy. The rolled plate is then solution treated at 850℃~870℃ for 1h to further spheroidize and appropriately grow the equiaxed α phase, while controlling the volume fraction of the equiaxed α phase. The rolled plate is then kept at 800℃~830℃ for 0.5h and then furnace cooled to 760℃~790℃ to promote the coarsening of some α sheets to make them rod-shaped α S Phase. Finally, the rolled plate is aged at 500℃~550℃ for 5h~8h to precipitate finer α in the β matrix to form a β transformation matrix. Through the combined effect of the above steps, a equiaxed α p A high-strength and high-toughness dual-phase titanium alloy with a three-level α phase structure consisting of a rod-shaped α lamella and a fine needle-shaped α phase in a β-transformed matrix. p The volume fraction of the phase is 15%~25%, and the volume fraction of the rod-shaped α sheet is 34%~45%.

[0049] In summary, this application firstly refines the structure, improves the strength of the alloy, and increases the Mo equivalent by adding an appropriate amount of Mo element based on the principle of composition modification; then, through a multi-pass small deformation variable temperature rolling process and a multi-stage heat treatment system, the interaction mechanism of recrystallization and phase transformation of titanium alloy under thermal-mechanical coupling conditions is used to obtain a multi-level α phase to improve the deformation coordination ability and impact toughness of the alloy. Mechanical property tests show that the tensile strength of this type of titanium alloy is greater than 1250MPa, the yield strength is greater than 1150MPa, the elongation after fracture is greater than 8%, and the impact toughness is greater than 35J / cm 2This type of titanium alloy has excellent strength and toughness and outstanding comprehensive mechanical properties, and will have broad application prospects and development potential in various fields of industry.

[0050] The following is explained in conjunction with specific embodiments:

[0051] Example 1

[0052] The high-strength and high-toughness dual-phase titanium alloy with a multi-level α-phase structure in this embodiment is composed of the following elements in mass percentage: Al: 5.16%, V: 7.47%, Si: 0.47%, Mo: 0.93%, and the remainder is Ti and some impurity elements.

[0053] The high-strength and high-toughness dual-phase titanium alloy with a multi-level α-phase structure in this embodiment is prepared as follows:

[0054] Titanium sponge, high-purity aluminum blocks, high-purity vanadium sheets, high-purity silicon particles and zirconium sponge were weighed and prepared according to the mass percentage of the elements, and the initial cast ingot was obtained after six smelting passes in a vacuum non-consumable arc furnace (the last three passes were smelted with magnetic stirring).

[0055] The round ingot is placed in a box furnace at 800℃, heated to 940℃ with the furnace without insulation treatment, and immediately hot-rolled on the two-roll mill for two passes, and returned to the furnace for insulation for 5 minutes between passes. The cumulative deformation of the two hot rolling passes is 30%. After the first two hot rolling passes are completed, the round ingot is quickly returned to the box furnace, and the furnace temperature parameters are reset to reduce it to 880℃ with the furnace for insulation for 10 minutes, and then the round ingot is hot-rolled on the two-roll mill for three passes, and returned to the furnace for insulation for 5 minutes between passes. The cumulative deformation of the three hot rolling passes is 50%. The total deformation of the five hot rolling passes is 80%. Finally, a rolled plate with a length of about 70mm, a width of 50mm, and a height of 6mm is obtained. The rolled plate after hot rolling is water quenched.

[0056] Put the rolled plate into the vacuum diffusion welding furnace and evacuate until the vacuum degree reaches 1×10 -3 After Pa, the temperature is raised to 580℃, pressurized for 2T and kept warm for 4h, the rolled plate is leveled and stress-relief annealed, and then taken out after furnace cooling.

[0057] The rolled plate was placed in a box furnace, subjected to solution treatment at 870°C for 1 hour, and then air-cooled. The rolled plate was then placed in a box furnace, kept at 820°C for 0.5 hour, and then cooled to 780°C with the furnace, and then air-cooled. Finally, the rolled plate was subjected to aging treatment at 550°C in a box furnace for 6 hours, and then air-cooled.

[0058] Wire cutting is performed in the middle position of the rolled plate to machine out tensile specimens and impact specimens respectively. The tensile specimen is a plate-shaped specimen with a cross-sectional size of 2mm×1.5mm and a gauge section of 8mm. The impact specimen is a V-mouth impact specimen with a size of 55mm×10mm×2.5mm. After the thermal deformation processing and subsequent heat treatment in the above steps, the room temperature mechanical properties of the high-strength and high-toughness dual-phase titanium alloy with multi-level α-phase structure in this embodiment are as follows after tensile and impact tests: tensile strength 1263MPa, yield strength 1152MPa, elongation after fracture 7.9%, impact toughness 34.8 / cm 2 .

[0059] Figure 1 The microstructure SEM image of the high-strength and high-toughness dual-phase titanium alloy with multi-level α phase structure prepared in this embodiment is a three-state structure consisting of equiaxed α p The three-level α phase structure consists of α phase, rod-shaped α sheets and fine needle-shaped α phase in the β transformation matrix. p The volume fraction of the phase is about 15.89%, the volume fraction of the coarsened rod-shaped α lamellae is about 45.76%, and the rest of the structure is a β-transformed matrix, in which finer secondary α phases are precipitated. p The irregular distribution of the phase and the coarsened α-lamellar community plays a role in coordinating deformation and increasing crack propagation paths, which can significantly improve the impact toughness of titanium alloys.

[0060] Figure 2 This is a high-magnification SEM image of the microstructure of the high-strength and high-toughness dual-phase titanium alloy with multi-level α phase structure prepared in this embodiment. p The average size of the phase is about 4.48μm, and the average length of the coarsened α sheet is about 5.27μm. The lamellar α phase with a certain aspect ratio formed by thermal deformation and subsequent heat treatment can improve the fracture toughness and crack growth ability of the alloy.

[0061] Figure 3 This is a tensile specimen fracture diagram of a high-strength and high-toughness dual-phase titanium alloy with a multi-level α-phase structure prepared in this embodiment. At the specimen fracture, it can be clearly seen that the central area surrounded by the edge of the shear lip presents a large area of ​​fiber area, and the overall cross section is not smooth. Further observation at a higher magnification revealed that there were large and deep dimples distributed at the fracture, indicating that the specimen underwent significant plastic deformation during the tensile process.

[0062] Example 2

[0063] The high-strength and high-toughness dual-phase titanium alloy with a multi-level α-phase structure in this embodiment is composed of the following elements in mass percentage: Al: 5.07%, V: 7.62%, Si: 0.42%, Mo: 0.95%, and the remainder is Ti and some impurity elements.

[0064] The high-strength and high-toughness dual-phase titanium alloy with a multi-level α-phase structure in this embodiment is prepared as follows:

[0065] Titanium sponge, high-purity aluminum blocks, high-purity vanadium sheets, high-purity silicon particles and zirconium sponge were weighed and prepared according to the mass percentage of the elements, and the initial cast ingot was obtained after six smelting passes in a vacuum non-consumable arc furnace (the last three passes were smelted with magnetic stirring).

[0066] The round ingot is placed in a box furnace at 800℃, heated to 940℃ with the furnace without insulation treatment, and immediately hot-rolled on the two-roll mill for two passes, and returned to the furnace for insulation for 5 minutes between passes. The cumulative deformation of the two hot rolling passes is 30%. After the first two hot rolling passes are completed, the round ingot is quickly returned to the box furnace, and the furnace temperature parameters are reset to reduce it to 880℃ with the furnace for insulation for 10 minutes, and then the round ingot is hot-rolled on the two-roll mill for three passes, and returned to the furnace for insulation for 5 minutes between passes. The cumulative deformation of the three hot rolling passes is 50%. The total deformation of the five hot rolling passes is 80%. Finally, a rolled plate with a length of about 70mm, a width of 50mm, and a height of 6mm is obtained. The rolled plate after hot rolling is water quenched.

[0067] Put the rolled plate into the vacuum diffusion welding furnace and evacuate until the vacuum degree reaches 1×10 -3 After Pa, the temperature is raised to 580℃, pressurized for 2T and kept warm for 4h, the rolled plate is leveled and stress-relief annealed, and then taken out after furnace cooling.

[0068] The rolled plate was placed in a box furnace, subjected to solution treatment at 870°C for 1 hour, and then air-cooled. The rolled plate was then placed in a box furnace, kept at 820°C for 0.5 hour, and then cooled to 780°C with the furnace, and then air-cooled. Finally, the rolled plate was subjected to aging treatment at 550°C in a box furnace for 6 hours, and then air-cooled.

[0069] Wire cutting is performed in the middle position of the rolled plate to machine out tensile specimens and impact specimens respectively. The tensile specimen is a plate-shaped specimen with a cross-sectional size of 2mm×1.5mm and a gauge section of 8mm. The impact specimen is a V-mouth impact specimen with a size of 55mm×10mm×2.5mm. After the thermal deformation processing and subsequent heat treatment in the above steps, the room temperature mechanical properties of a high-strength and high-toughness dual-phase titanium alloy with a multi-level α-phase structure in this embodiment are as follows: tensile strength 1255MPa, yield strength 1156MPa, elongation after fracture 8.2%, impact toughness 35.4 / cm 2 .

[0070] Figure 4 is a microstructure SEM image of the high-strength and high-toughness dual-phase titanium alloy with multi-level α phase structure prepared in this embodiment, and its organizational morphology is also a three-state structure. p The volume fraction of the phase is about 24.02%, the volume fraction of the coarsened rod-shaped α lamellae is about 34.41%, and the rest of the structure is a β-transformed matrix, in which there are fine α lamellae precipitated during the low-temperature aging process.

[0071] The mechanical property test results of the two embodiments are shown in Table 1.

[0072] Table 1 Mechanical properties test results of Example 1 and Example 2

[0073] Tensile strength(MPa) Yield strength (MPa) Elongation after break (%) <![CDATA[Impact toughness (J / cm 2 )]]> Example 1 1263 1152 7.9 34.8 Example 2 1255 1156 8.2 35.4

[0074] In summary, the high-strength and high-toughness dual-phase titanium alloy with a multi-level α-phase structure designed and prepared by this application has relatively excellent strength-plasticity-toughness matching and relatively outstanding comprehensive mechanical properties, which can meet the needs of products in various industrial fields.

[0075] It should be noted that, in this article, terms such as "comprises", "includes" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or apparatus that includes a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or apparatus.

[0076] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A high-strength and high-toughness dual-phase titanium alloy with a multi-level α-phase structure, characterized in that: The mass percentages of the titanium alloy elements are as follows: Al: 4.8%-5.2%, V: 7.3-7.8%, Si: 0.3-0.5%, Mo: 0.8-1.1%, the remainder being Ti and impurity elements, and the mass percentages of Al, V, Mo, and Si elements must satisfy the following relationship: ; Among them, W Al , W Si , W V , W Mo Refers to the mass percentage of Al, Si, V, and Mo elements respectively; The preparation method of the titanium alloy comprises: The ingredients are prepared according to the composition ratio of the high-strength and high-toughness dual-phase titanium alloy, and an initial titanium alloy ingot is obtained by smelting; The initial titanium alloy ingot is subjected to a multi-pass hot rolling treatment to obtain a titanium alloy rolled plate, wherein the multi-pass hot rolling treatment comprises: placing the initial titanium alloy ingot in a heat treatment furnace at 800°C to 830°C, heating the initial titanium alloy ingot to 930°C to 970°C with the furnace, and immediately rolling the initial titanium alloy ingot for two passes, returning the ingot to the furnace for insulation for 5min to 8min between passes; then cooling the initial titanium alloy ingot to 880°C to 900°C with the furnace, and after insulation for 5min to 10min, rolling the ingot for three passes and finally quenching the ingot, returning the ingot to the furnace for insulation for 5min to 8min between passes, and the total rolling deformation is 70% to 80%; The titanium alloy rolled plate is subjected to vacuum pressurization leveling treatment, stress relief annealing treatment, solution treatment and aging treatment to obtain a final high-strength and high-toughness dual-phase titanium alloy with a multi-level α phase structure.

2. The high-strength and high-toughness dual-phase titanium alloy with a multi-level α-phase structure according to claim 1, characterized in that: The titanium alloy has a tensile strength greater than 1250 MPa, a yield strength greater than 1150 MPa, a post-fracture elongation greater than 8%, and an impact toughness greater than 35 J / cm 2 .

3. The high-strength and high-toughness dual-phase titanium alloy with a multi-level α-phase structure according to claim 1, characterized in that: The titanium alloy structure includes equiaxed α p phase, rod-shaped α sheets and β transformation matrix, and the β transformation matrix contains fine secondary α phase.

4. The high-strength and high-toughness dual-phase titanium alloy with a multi-level α-phase structure according to claim 3, characterized in that: The isometric α p The volume fraction of the phase is 15% to 25%, and the volume fraction of the rod-like α sheet is 34% to 45%.

5. A method for preparing a high-strength and high-toughness dual-phase titanium alloy with a multi-level α-phase structure, characterized in that: include: The ingredients are prepared according to the composition ratio of the high-strength and high-toughness dual-phase titanium alloy according to any one of claims 1 to 4, and an initial titanium alloy ingot is obtained by smelting; The initial titanium alloy ingot is subjected to a multi-pass hot rolling treatment to obtain a titanium alloy rolled plate; the multi-pass hot rolling treatment comprises: placing the initial titanium alloy ingot in a heat treatment furnace at 800°C to 830°C, heating the initial titanium alloy ingot to 930°C to 970°C with the furnace, and immediately rolling the initial titanium alloy ingot for two passes, returning the furnace to keep the temperature for 5min to 8min between passes; then cooling the initial titanium alloy ingot to 880°C to 900°C with the furnace, keeping the temperature for 5min to 10min, rolling the initial titanium alloy ingot for three passes and finally quenching, returning the furnace to keep the temperature for 5min to 8min between passes, and the total rolling deformation is 70% to 80%; The titanium alloy rolled plate is subjected to vacuum pressurization leveling treatment, stress relief annealing treatment, solution treatment and aging treatment to obtain a final high-strength and high-toughness dual-phase titanium alloy with a multi-level α phase structure.

6. The method for preparing a high-strength and high-toughness dual-phase titanium alloy having a multi-level α-phase structure according to claim 5, characterized in that: The stress relief annealing treatment is performed at 560° C. to 600° C. for 3 h to 5 h.

7. The method for preparing a high-strength and high-toughness dual-phase titanium alloy having a multi-level α-phase structure according to claim 5, characterized in that: The solution treatment is to perform a solution treatment on the rolled plate after stress relief annealing at 850° C. to 870° C. for 1 hour and then air cool it.

8. The method for preparing a high-strength and high-toughness dual-phase titanium alloy having a multi-level α-phase structure according to claim 7, characterized in that: The aging treatment is to keep the rolled plate after solution treatment at 800°C-830°C for 0.5h, cool it to 760°C-790°C with the furnace, and then air-cool it. Then, carry out aging treatment at 500°C-550°C for 5h-8h and then air-cool it.

Citation Information

Patent Citations

  • High-strength and high-plasticity metastable-state beta-type titanium alloy and preparation method thereof

    CN113862514A

  • Titanium alloy casting having high strength and high toughness

    JP1996041565A